Structure, Educational Value and Use of Folklore Books “Dongeng Rakyat Kabupaten Rembang Jilid I” as an Alternative for High School Teaching Material - Kusumawati, Dita Ayu; Nuryatin, Agus; Doyin, Mukh (Universitas Negeri Semarang, 2021)
The values ​​contained in folklore can shape a person's character. In folklore, speakers not only provide entertainment and indirectly the elements contained in the story in giving thoughts to someone, so that it will form a character. Fairy tales are a form of folklore that contains educational values ​​including moral, heroic, religious, social, and cultural values. Therefore, fairy tales can be used as literature teaching materials in schools, especially at the high school level. Students at that time increasingly needed supporting components to shape their character, but the lack of literary teaching materials could affect the character development of students to be not optimal, so alternative teaching materials were needed. The fairy tales contained in the “Dongeng Rakyat Kabupaten Rembang Jilid I” book can be an alternative for teaching literature in schools, this is because Rembang Regency is a coastal area that has been largely influenced by foreign cultures, but until now they have been able to maintain their original culture. This study uses a pragmatic approach in the analysis of the narrative structure using the structuralism theory of Vladimir Yakovlevich Propp which consists of 31 units of narrative structure which are then divided into 7 action circles to facilitate the process of analyzing the educational value contained in it. This study used the descriptive qualitative method. A collection of folk tales in Rembang Regency include the Origin of “Asal Usul Desa Sulang”, “Cerita Rakyat Yuyu Rumpung”, and “Riwayat Terjadinya Desa Kaliori” this study concludes that the Rembang Regency folktale book is suitable to be used as alternative teaching material in high school because it contains educational values, namely heroism, social, cultural, and religious values ​​that are needed for the process of forming student character in modern times like today.